Entering the KIBS' black box: there must be an angel! (or is there something like a knowledge angel?) - Emmanuel Muller; Andrea Zenker; Jean-Alain Héraud (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2009)
The undeniable importance of knowledge and innovation in modern economies justifies the increasing interest that scholars are taking in studying knowledge-intensive busi-ness services (KIBS). Since the mid 1990s, there has been a significant increase in the attention paid to KIBS and their role and functions in innovation systems (den Hertog 2000; Illeris 1991; Miles et al. 1995; Muller/Zenker 2001; Strambach 2001; Tether 2005; Wood 2002). In general terms, the activity of KIBS can be mainly described as the provision of knowledge-intensive inputs to the business process of other organiza-tions, private as well as public sector clients. [...] To sum up, this paper focuses on creative individuals in KIBS, i.e. those persons sus-pected of playing a pertinent role with respect to the innovativeness of their company. We call these specific actors knowledge angels by analogy with business angels. In the same way that business angels can play a decisive role in the development of innova-tive firms through financial support, we assume here that specifically gifted persons can be the knowledge 'catalysts' within KIBS (and in relationship with their clients). The paper contains three sections: the first one formulates the assumption of the exis-tence of knowledge angels and attempts to elaborate a working definition of this spe-cific kind of actor. The second section displays the results of an empirical research pro-ject conducted in France and Germany, whereas the third section synthesizes the find-ings.
urn:nbn:de:0011-n-1021704
Keywords: 330; Wissen; Business Angels; Unternehmensdienstleistung; Innovation; Deutschland; Frankreich